Impacts of job demands on nurses' performance working in public hospitals - Al-Homayan, Abdullah Mohammad; Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan; Islam, Rabiul (Science Publications, 2013)
Job demands refers to the degree to which the working environment contains stimuli that require some effort, which suggests that job demands may lead to negative consequences if they require additional effort to achieve work goals.The aim of the study is to analysis the impacts of job demands on nurses’ performance working in public hospitals.In order to achieve the study objective, a survey conducted.Questionnaires distributed to the public sector hospital’s manager in Saudi Arabia.The findings of the study turn out to be true; the study will contribute to both theory and practice.Through the present study, the researcher expects the findings to shed light on the research conducted regression to analysis the impacts of job demands on nurses’ performance.